Vitor Quality of Life Scale for the elderly: Construction - José Vitor da Silva; Makilim Nunes Baptista (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2019)
The objective of this study was to describe the conceptual model and construction of the Vitor Quality of Life Scale for the Elderly (VITOR QLSE). The following approaches were employed to devise and incorporate new items and dimensions into the scale: qualitative study, literature review, focus group and pre-test performed in 30 older adults. The VITOR QLSE was constructed based on the structure of the Quality of Life Index (QLI) and on a specific methodological structure providing dimensions reflecting the quality of life of older adults. The present instrument may serve as a valuable resource in healthcare practice and research that meets the needs of the scientific community, especially in light of the current dearth of instruments in this area.